Impact of forest certification: from the perspective of forest concessionaires' staffs - Mohamad Zainalabidin, Syahaneem; Mohamed, Shukri (2011)
Concerned by the increased in tropical deforestation, a number of efforts to combat deforestation and forest degradation due to the bad management of forest practices were raised by several parties. As a result, forest certification was introduced as a tool to improve forest management practices which among the rationales is to assure that the forest management is compliance with social, economic and environmental sustainability principles. This paper analyses the impact of the forest certification towards social, economy and environment from the view of three forest concessionaire companies’ staffs. Since the introduction of forest certification to these companies, a lot of changes have been made to ensure the companies operation is compliance with the principle and criteria of the forest certification. Assessing it, from the staffs’ view are essential because they involved in every aspects of forest management. Results reveal that certification had lead to more positive impacts such as benefited the staffs’ social welfare and help in improving the sustainability of forest. However, the implementation of the program has been affecting these companies economically due to the additional cost of getting certified and annual inspection. On this other hand, this research exposes the impacts of forest certification and hopefully, it has provided useful information for the stakeholders regarding the issues on forest certification